The netherworld in ancient Egypt and China an imagined paradise - Pu, Muzhou 1952- (Bloomsbury Academic, 2023)
"Considering the striking similarities between the treatment of the dead and conceptions of the netherworld in ancient Egypt and China, how can these traditions be compared? In this book, Mu-chou Poo considers this question, and provides a new perspective on archaeological materials, including tomb structures and funerary texts, by addressing them in the context of universal human problems such as death, the future of the dead, and the search for happiness in life. To frame his analysis, Poo chronologically reconstructs the emergence of the idea of netherworld and its evolution in both ancient Egypt and ancient China. He explores the relationship between religious beliefs and social ethics in these civilizations, and looks at the reasons why similar social and material conditions could have produced varied expressions of the afterlife, and what such variations reveal about each of the parties in question. Poo argues that a comparison between both visions of the netherworld and their relationship to life experience enables us to gain further insight into the nature of each culture. Additionally, through his analysis, he shows that thematic comparison of ancient civilizations is not only possible, but extremely relevant to modern society."
Keywords: Jenseitsglaube; Brauch; Tod; Ägypten -- Altertum; China; Future life; Happiness / Religious aspects; Egypt / Religion; China / Religion; Ancient Egypt; Ancient religions & mythologies